Profit Maximization Of SAAS By Reusing The Available VM Space In Cloud Computing (International Journal of Engineering and Computer Science, 2015)
Cloud computing has recently emerged as one of the buzzwords in the IT industry. SaaS layer is the upper layer of the cloud-computing model. It offers consistent access to software applications to the clients over the Internet without direct investment in infrastructure and software. It is a service provided to client in terms of applications running on the cloud-computing infrastructure hosted by the service providers. The main work of this layer is to deliver the software application services over the internet with in the real time when users demand for it in pay per use manner. The main concern of this paper is on how to minimize the infrastructure cost and maximize the SaaS provider profit for that two algorithms are proposed. The proposed algorithms are designed in such a way that works on the mean value which efficiently uses the available VM Space to handle the client request instead of creating a new VM to deliver the services. And by that the SAAS provider has not to pay the extra penalty cost and hence they get a profit to serve the request of clients with their satisfaction and without violation of SLA.